The Virgin way everything I know about leadership - Branson, Richard (New York Penguin, 2014)
While building the Virgin Group over forty years, Richard Branson has never shied away from seemingly outlandish challenges that others (including his own colleagues on several occasions) considered sheer lunacy. He has taken on giants like British Airways and won, and monsters like Coca-Cola and lost. Now Branson gives an inside look at his strikingly different swashbuckling style of leadership. Learn how fun, family, passion, and the dying art of listening are key components to what his extended family of employees around the world have always dubbed (with a wink) the "Virgin Way." This unique perspective comes from a man who dropped out of school at sixteen, suffers from dyslexia, and has never worked for anyone but himself. He may be famous for thinking outside the box-an expression he despises-but Branson asserts that "you'll never have to think outside the box if you refuse to let anyone build one around you." This is a unique book on leadership from someone who readily admits he has never read a book on leadership in his life. So expect the unexpected
Includes index.
Keywords: Leadership